Fluoxetine inhibited RANKL-induced osteoclastic differentiation in vitro - Zhang Jing-wen; Zhao Fang-bing; Ma Bing’er; Shen Xiao-qing; Geng Yuan-ming (Open Medicine)
Selective serotonin reuptake inhibitor correlates with decreased bone mineral density and impedes orthodontic tooth movement. The present study aimed to examine the effects of fluoxetine on osteoclast differentiation and function. Human peripheral blood mononuclear cells (hPBMCs) and murine RAW264.7 cells were cultured with RANKL to stimulate osteoclast differentiation. The resulting multinucleated cells displayed characteristics of mature osteoclasts. Fluoxetine at 0.01–1 μM did not impact cellular viability or oxidative stress. However, 10 μM fluoxetine significantly reduced clonal growth, cell viability, and increased cytotoxicity and lipid peroxidation in RAW 264.7 cells. Further, application of 0.1 μM fluoxetine potently suppressed osteoclast differentiation of both RAW264.7 and hPBMCs, with reduced osteoclast numbers and downregulation of osteoclastic genes matrix metalloproteinase-9, cathepsin K, and integrin β3 at mRNA and protein levels. Fluoxetine also disrupted F-actin ring formation essential for osteoclast resorptive function. Mechanistically, fluoxetine inhibited NF-kB signaling by reducing phosphorylation of pathway members IκBα and p65, preventing IκBα degradation and blocking p65 nuclear translocation. In conclusion, this study demonstrates fluoxetine suppressing osteoclast differentiation in association with disrupting NF-kB activation, providing insight into orthodontic treatment planning for patients taking fluoxetine.